Treatment of Periprosthetic Infections: An Economic Analysis. (28th May 2013) - Hernández-Vaquero, Daniel; Fernández-Fairen, Mariano; Torres, Ana; Menzie, Ann M.; Fernández-Carreira, José Manuel; Murcia-Mazon, Antonio; Guerado, Enrique; Merzthal, Luis
Abstract : This review summarizes the existing economic literature, assesses the value of current data, and presents procedures that are the less costly and more effective options for the treatment of periprosthetic infections of knee and hip. Optimizing antibiotic use in the prevention and treatment of periprosthetic infection, combined with systemic and behavioral changes in the operating room, the detection and treatment of high-risk patient groups, as well as the rational management of the existing infection by using the different procedures according to each particular case, could allow for improved outcomes and lead to the highest quality of life for patients and the lowest economic impact. Nevertheless, the costeffectiveness of different interventions to treat periprosthetic infections remains unclear.